Compact heterodyne NEMS oscillator for sensing applications. (November 2016) - Sansa, Marc; Gourlat, Guillaume; Jourdan, Guillaume; Gely, Marc; Villard, Patrick; Sicard, Gilles; Hentz, Sébastien
Abstract: We present a novel topology of heterodyne nanoelectromechanical self-oscillator, aimed at the dense integration of resonator arrays for sensing applications. This oscillator is based on an original measurement method, suitable for both open loop and closed loop operations, which simplifies current down-mixing set-ups. When implemented on-chip, it will allow the reduction of the size and power consumption of readout CMOS circuitry. This is today the limiting factor for the integration density of NEMS oscillators for real-life applications. Here we characterize this method in both open-loop and closed-loop, and evaluate its frequency stability.